Identification of proteins involved in inhibition of spheroid formation under microgravity. Issue 17 (11th June 2015) - Riwaldt, Stefan; Pietsch, Jessica; Sickmann, Albert; Bauer, Johann; Braun, Markus; Segerer, Juergen; Schwarzwälder, Achim; Aleshcheva, Ganna; Corydon, Thomas J; Infanger, Manfred; Grimm, Daniela
<x xml:space="preserve">Abstract</x> Many types of cells transit in vitro from a two‐ to a three‐dimensional growth, when they are exposed to microgravity. The underlying mechanisms are not yet understood. Hence, we investigated the impact of microgravity on protein content and growth behavior. For this purpose, the human thyroid cancer cells FTC‐133 were seeded either in recently developed cell containers that can endure enhanced physical forces and perform media changes and cell harvesting automatically or in T‐25 culture flasks. All cells were cultured for five days at 1g. Afterwards, a part of the cell containers were flown to the International Space Station, while another part was kept on the ground. T‐25 flasks were mounted on and next to a Random Positioning Machine. The cells were cultured for 12 days under the various conditions, before they were fixed with RNAlater. All fixed cultures showed monolayers, but three‐dimensional aggregates were not detected. In a subsequent protein analysis, 180 proteins were identified by mass spectrometry. These proteins did not indicate significant differences between cells exposed to microgravity and their 1g controls. However, they suggest that an enhanced production of proteins related to the extracellular matrix could detain the cells from spheroid formation, while profilin‐1 is phosphorylated.